Respon Pujian Narasumber Wanita Pada Podcast Youtube Vindes - Regina Delviani Putri; Wawan Gunawan; Chye Retty Isnendes (Peneliti.net, 2023)
ABSTRACT This article aims to identify the responses of female guest speakers to praise on the YouTube podcast Vindes. This research utilizes a qualitative descriptive method. The data for this study consists of speech transcripts. The data collection technique employed in this research is note-taking, using the interactive analysis model technique. The results of this study indicate that female guest speakers utilize various types of responses to praise, such as appreciation tokens, comment acceptance, comment history, reassessment, return, disagreement, qualification, no acknowledgment, and a combination. The Female guest speakers on the YouTube podcast Vindes demonstrate differences in their use of praise responses, which are influenced by factors such as proximity and career background. Keywords: podcast, praise, response